Construction of Three-Dimensional Conductive Graphitic Architecture by Highly Efficient Electrochemical Exfoliation - Huang, Yang; Xu, Xiao; Wang, Ying; Zhu, Wenyou; Zhuang, Wenchang; Song, Ming (Frontiers in Energy Research, 2021)
Graphene has long been envisioned as a promising material in areas, such as energy storage, electromagnetic shielding, and electrochemical sensor. However, the fabrication of graphene is complicated, time-consuming, and hazardous to environment, and thus can hardly realize industrialization. Although the exfoliation of graphite through electrochemical method was believed as an efficient and green approach, the intense current and non-protective action usually lead to the total destruction of the integralgraphitic electrode. In this work, the graphite foil was well-exfoliated into few-layered graphene with proper electrolyte compositions and electrochemical technique. Moreover, the original three-dimensional (3D) integrity of graphite foil can be maintained with the assistance of space-confined exfoliation strategy. The exfoliation process was systematically investigated in terms of electrolyte, applied potential, cation, and anion. The optimized sample exhibited an almost 8.0-folds of increment of double-layer capacitance in comparison with the pristine graphite foil. Eventually, the chemical simulations were employed to elaborate the mechanisms of advanced exfoliation. The space-confined exfoliation reported here is promising for scalable fabrication of 3D graphene materials.